Safety of cinacalcet in children and adolescents with chronic kidney disease-mineral bone disorder: systematic review and proportional meta-analysis of case series - Zamoner, Soraya Mayumi Sasaoka [UNESP] (2024)
Background: Mineral and bone disease in children with chronic kidney disease can cause abnormalities in calcium, phosphorus, parathyroid hormone, and vitamin D and when left untreated can result in impaired growth, bone deformities, fractures, and vascular calcification. Cinacalcet is a calcimimetic widely used as a therapy to reduce parathyroid hormone levels in the adult population, with hypocalcemia among its side effects. The analysis of safety in the pediatric population is questioned due to the scarcity of randomized clinical trials in this group. Objective: To assess the onset of symptomatic hypocalcemia or other adverse events (serious or non-serious) with the use of cinacalcet in children and adolescents with mineral and bone disorder in chronic kidney disease. Data sources and study eligibility criteria: The bibliographic search identified 2699 references from 1927 to August/2023 (57 LILACS, 44 Web of Science, 686 PubMed, 131 Cochrane, 1246 Scopus, 535 Embase). Four references were added from the bibliography of articles found and 12 references from the gray literature (Clinical Trials). Of the 77 studies analyzed in full, 68 were excluded because they did not meet the following criteria: population, types of studies, medication, publication types and 1 article that did not present results (gray literature). Participants and interventions: There were 149 patients aged 0–18 years old with Chronic Kidney Disease and mineral bone disorder who received cinacalcet. Study appraisal and synthesis methods: Nine eligible studies were examined for study type, size, intervention, and reported outcomes. Results: There was an incidence of 0.2% of fatal adverse events and 16% of serious adverse events (p < 0.01 and I2 = 69%), in addition to 10.7% of hypocalcemia, totaling 45.7% of total adverse events. Limitations: There was a bias in demographic information and clinical characteristics of patients in about 50% of the studies and the majority of the studies were case series. Conclusions and implications of key findings: If used in the pediatric population, the calcimimetic cinacalcet should be carefully monitored for serum calcium levels and attention to possible adverse events, especially in children under 50 months. Systematic review registration number (PROSPERO register): CRD42019132809.